KUALITAS PENGEMBANGAN KECAMATAN LAYAK ANAK (KELANA) DAN DESA/KELURAHAN LAYAK ANAK (DEKALA) DI KABUPATEN BANTUL - Fauzian Nur Azizah; Safira Zata Yumni; Maska Septafiya Angesti; Andreas Deddy Eko Nugroho (Badan Perencanaan Pembangunan Daerah Kabupaten Bantul, 2023)
Fulfillment and protection children's rights as the main objective of implementing Kabupaten Layak Anak (KLA) in Bantul Regency needs to be carried out comprehensively and in stages starting from kabupaten, kapanewon, and kalurahan. Kecamatan and Kelurahan Layak Anak must be developing to achieve Kabupaten Layak Anak. This research was conducted to determine the development quality of Kecamatan and Kelurahan Layak Anak (KELANA/DEKALA) in Bantul Regency. This research method uses a quantitative-descriptive approach. The parameters used are indicators of Kecamatan and Kelurahan Layak Anak, which include regulations/policies, programs/activities, and supporting infrastructure for KELANA and DEKALA in each kalurahan and kapanewon in Bantul Regency. Based on the research results, proven that 1) The quality development of kapanewon and kalurahan Layak Anak in Bantul Regency was mostly categorized as quite good, 2) All of the kapanewon and kalurahan in Bantul Regency already has regulations supporting the fulfillment and protection of children's rights, 3) Program/activities development supporting Kecamatan Layak Anak in Bantul Regency are still not good, while the development of Program/activities supporting Kelurahan Layak Anak in Bantul Regency is good, 4) Kapanewon and Kalurahan office's infrastructure quality in Bantul Regency is good because they have provided infrastructure that is used as a benchmark in developing Kecamatan and Kelurahan Layak Anak, even though most do not yet fill the highest standards.